Influenza hemagglutination inhibiting activity in respiratory mucus from horses with chronic obstructive pulmonary disorders (heaves syndrome). - Thorsen, J (1983)
Samples of mucus from the lower trachea were collected from 53 horses with chronic obstructive pulmonary disease and from 24 clinically normal horses. Serum samples were collected from 35 of the horses with chronic obstructive pulmonary disease and from the 24 normal horses. Samples were tested for inhibition of hemagglutination by influenza A equine 1 and 2 viruses. There were high levels of hemagglutination inhibiting activity against influenza A equine 1 in mucus samples from horses with chronic obstructive pulmonary disease.